Hydrodynamic Interaction of Elastic Capsules in Bounded Shear Flow (Communications in Computational Physics, 2014)
This paper presents a modified Loop's subdivision algorithm for studyingthe deformation of a single capsule, the hydrodynamic interaction between two capsules and the hydrodynamic diffusion of a suspension of capsules in bounded shearflow. A subdivision thin-shell model is employed to compute the forces generated onthe surface of the elastic capsule during deformation. The capsule surface is approximated using the modified Loop's subdivision scheme which guarantees bounded curvature and $C^1$ continuity everywhere on the limit surface. The present numerical technique has been validated by studying the deformation of a spherical capsule in shearflow. Computations are also performed for a biconcave capsule over a wide range ofshear rates and viscosity ratios to investigate its dynamics. In addition, the hydrodynamic interaction between two elastic capsules in bounded shear flow is studied.Depending on the wall separation distance, the trajectory-bifurcation points that separate reversing and crossing motions for both spherical and biconcave capsules can befound. Compared to the spherical capsules, the biconcave capsules exhibit additionaltypes of interaction such as rotation and head-on collision. The head-on collision results in a large trajectory shift which contributes to the hydrodynamic diffusion of asuspension. A suspension of a large number of biconcave capsules in shear flow isalso simulated to show the ability of the modified scheme in running a large-scalesimulation over a long period of time.